Neurological levels of thinking and entrepreneurship for post-pandemic economic revival (Journal of Namibian Studies : History Politics Culture, 2023)
Understanding our mind allows us to know ourselves better. The neurological levels of thinking allow us to identify the level of conflict and its relationship with entrepreneurial behavior and entrepreneurship, in order to achieve a reactivation of the post-pandemic economy. The study was conducted using a quantitative-qualitative approach and a descriptive level, which allowed us to identify the conflict at the level of thinking in which the student is located: environment, behavior, habits, beliefs, identity, and transcendence. It was applied to a population of students from ESPOCH's Faculty of Business Administration in five majors (Accounting and Auditing, Marketing, Transportation Management, Finance and Business Administration), with a total population of 981 students enrolled in the subject of entrepreneurship. The study was applied to the entire population, except for 2% of students who did not attend in-person classes due to some domestic calamity or other reasons. The results show non-constructive environments, negative behaviors, untapped capacities, and the highest level of conflict being limiting beliefs towards entrepreneurship and money, as well as an unidentified identity. It is concluded that the neurological levels of thinking can be modified thanks to neuroplasticity, which facilitates changes in behavior and habits towards entrepreneurship, resulting in a post-pandemic economic reactivation. Those who undertake directly impact the development of their reality, and their beliefs and entrepreneurial values are related to personal motivation, with the capacity to create a transformative and social change.